Physicochemical, Rheological, Structural, Antioxidant, and Antimicrobial Properties of Polysaccharides Extracted from Tamarind Seeds. (23rd February 2022) - Ren, Likun; Yang, Yang; Bian, Xin; Li, Xiaomei; Wang, Bing; Wang, Dangfeng; Su, Dan; Liu, Linlin; Yu, Dehui; Guo, Xiaoxue; Zhang, Xiumin; Zhang, Na
Abstract : In this study, the polysaccharides were firstly extracted from the tamarind seeds in which the crude polysaccharides have been extracted once by hot water extraction. The structure was characterized by FTIR, SEM, and X-ray diffraction after removing protein and small molecule impurities. Furthermore, the rheological and bioactivity of tamarind seed polysaccharides (TSP) were also investigated. The results indicated that the yield of the obtained polysaccharide was 3.42%. TSP was mainly composed of glucose (45.09%), galactose (22.80%), and xylose (28.89%), while it contained characteristic structure of polysaccharides, such as –OH, pyranose, and uronic acid at 3, 418, 1, 150, and 1, 040 cm −1 respectively, which demonstrated that it was a uronic acid heteropolysaccharide. Moreover, the XRD pattern revealed the amorphous behavior of TSP, and it was found to consist of films or "sheets" reflected by SEM. The flow behavior testing confirmed its pseudoplastic character, and the flow behavior index ( n ) was between 0.4539 and 0.9201. The DPPH radical scavenging activity of TSP was 40.34% at 10 mg/mL. Furthermore, TSP displayed moderate hydroxyl radical scavenging and anti-bacterial activities, owing to its special structure and composition. Overall, our results suggested that TSP could be used as a food ingredient with anti-oxidative and antibacterial activities, which provides useful information on the potential utilization of TSP in the food industry.